2015
DOI: 10.1108/scm-06-2015-0201
|View full text |Cite
|
Sign up to set email alerts
|

Modern slavery and the supply chain: the limits of corporate social responsibility?

Abstract: Purpose – This conceptual paper aims to examine modern slavery in the supply chain, showing how the issue challenges conventional thinking and practice in corporate social responsibility (CSR). Design/methodology/approach – The paper considers the differences between modern slavery and other concerns within CSR. It examines legal attempts to encourage supply chain transparency and the use of corporate CSR methods. An example of forced la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
212
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(237 citation statements)
references
References 59 publications
(56 reference statements)
2
212
0
4
Order By: Relevance
“…Other less frequently addressed sectors in conceptual SLCA research include agricultural crop production (Feschet et al. ; New ), construction of buildings (Lützkendorf and Lorenz ), electric power generation, transmission, and distribution (Norris ; Wood and Hertwich ), scientific research and development services (Meyer and Upadhyayula ), waste management and remediation services (Aparcana and Salhofer ), and other multiple (Chen and Delmas ; Labuschagne et al. ) sectors.…”
Section: Discussing the State Of Social Life Cycle Assessment Indicatmentioning
confidence: 99%
“…Other less frequently addressed sectors in conceptual SLCA research include agricultural crop production (Feschet et al. ; New ), construction of buildings (Lützkendorf and Lorenz ), electric power generation, transmission, and distribution (Norris ; Wood and Hertwich ), scientific research and development services (Meyer and Upadhyayula ), waste management and remediation services (Aparcana and Salhofer ), and other multiple (Chen and Delmas ; Labuschagne et al. ) sectors.…”
Section: Discussing the State Of Social Life Cycle Assessment Indicatmentioning
confidence: 99%
“…Sweatshop labor is the term often used to describe oppressive working conditions. The term is often synonymous with “modern slavery” (Gold, Trautrims & Trodd, ; New, ), which is pervasive in practice but has received less attention in the OSCM literature. This negligence applies also to workplace safety, better known as occupational health and safety (OHS) (Lo, Pagell, Fan, Wiengarten & Yeung, ).…”
Section: Supplier Sustainability: a Risk Perspectivementioning
confidence: 99%
“…This is essentially what we did when the Rana Plaza disaster occurred; but it was understandably not possible to obtain perfect symmetry between the before and after data (Huq et al 2016). New (2015) acknowledged that, in researching unsustainable social practices, researchers might find the data harder to collect and it could be necessary to adopt certain 'investigative journalist' approaches. As expected, given the sensitivity of the issues covered, access became more difficult and respondents were more reluctant to share information, and thus, it was not possible to conduct further interviews in all seven suppliers.…”
Section: Data Collectionmentioning
confidence: 99%
“…To conduct more substantive and critical work while investigating controversial social failures, it has been suggested that researchers should try to incorporate a wider view, i.e., to include more sources of information than the firms themselves and to try to understand the broader institutional context of the phenomena under exploration (New 2015). Therefore, similar to data collection before the Rana Plaza disaster, the post-Rana supplier interviews were also augmented by ten further interviews in four of the buyers, two NGOs, one labor union, and the Apparel Trade Body (see Table 2).…”
Section: Data Collectionmentioning
confidence: 99%